Lysine, methionine, phenylalanine, arginine, valine, isoleucine, leucine, and threonine maintenance requirements of broiler breeders - Sakomura, N. K. (2015)
Five hundred and sixty Cobb-Vantress broiler breeders were used to determine the maintenance requirement of dietary Arg, His, Ile, Leu, Lys, Met, Phe, Thr, and Val in 10 21-d assays using the comparative slaughter technique. Fifty sexually immature broiler breeder pullets per assay were given crystalline amino acid diets containing graded levels of Arg, His, Ile, Leu, Lys, Met, Phe, Thr, or Val, respectively, representing 0, 10, 20, 30, 40% of their suggested requirement level (NRC, 1994) with all other amino acids maintained at 40% of their suggested requirement level. Sixty hens were slaughtered prior to the beginning of the study to assess initial body composition at 3 weight groups. Linear regression lines (protein accretion vs. amino acid intake) were determined and the maintenance requirements were calculated based on zero protein accretion. The maintenance requirements expressed on a metabolic weight basis were determined to be 174, 94, 52, 81, 60, 126, 133, and 155 mg/kg0.75/d for Arg, Ile, Leu, Lys, Met, Phe, Thr, and Val, respectively. Additionally, the maintenance requirements, expressed on metabolic protein weight basis, were determined to be 651, 329, 172, 295, 223, 523, 478, and 546 mg/kgCP/d for Arg, Ile, Leu, Lys, Met, Phe, Thr, and Val, respectively. The requirement for His could not be established as the results obtained were outside of assay range.